Design and fabrication of a low cost desktop electrochemical 3D printer - Chen,X; Liu,X; Childs,P; Brandon,N; Wu,B (2018)
Copyright © 2018 by Nanyang Technological University. Additive manufacturing (AM) (3D printing) is the process of creating 3D objects from digital models through the layer by layer deposition of materials. Electrochemical additive manufacturing (ECAM) is a relatively new technique which can create metallic components based depositing adherent layers of metal ions onto the surface of conductive substrate. In this paper, the design considerations for a meniscus confined ECAM approach is presented which demonstrates superior print speeds to equivalent works. This is achieved through the increase of the meniscus diameter to 400 \im which was achieved through the integration of a porous sponge into the print head to balance the hydraulic head of the electrolyte. Other piston based methods of controlling the electrolyte meniscus are discussed.